Ferroptosis Characterization in Lung Adenocarcinomas Reveals Prognostic Signature With Immunotherapeutic Implication - Sun, Sijin; Yang, Yannan; Yang, Zhenlin; Wang, Juhong; Li, Renda; Tian, He; Tan, Fengwei; Xue, Qi; Gao, Yibo; He, Jie (Frontiers in Cell and Developmental Biology, 2021)
The iron-dependent cell death named ferroptosis has been implicated in the progression and therapeutic response of several tumors. However, potential role of ferroptosis in lung adenocarcinomas (LUAD) remained less well understood. In TCGA-LUAD cohort, unsupervised clustering was first conducted based on ferroptosis regulators extracted from FerrDb database. Comprehensive correlation analysis and comparisons were performed among ferroptosis subtypes. The ferroptosis-related prognostic (FRP) signature was identified based on filtered features and repeated LASSO and was validated in five independent cohorts. The clinical relevance between the risk score and therapeutic response was further explored by multiple algorithms. qPCR was implemented to verify gene expression. A total of 1168 LUAD patients and 161 ferroptosis regulators were included in this study. Three ferroptosis subtypes were identified and patients in subtype B had the best prognosis among the three subtypes. Significant differences in immune microenvironment and biological function enrichment were illustrated in distinct subtypes. The Boruta algorithm was conducted on 308 common differentially expressed genes for dimensionality reduction. A total of 56 genes served as input for model construction and a six-gene signature with the highest frequencies of 881 was chosen as FRP. The prognostic significance of FRP was validated in five independent cohorts. High FRP risk score was also linked to increased tumor mutation load, PD-L1 protein expression and number of neoantigens. 83.3% of the FRP genes were abnormally expressed in LUAD cell lines. In conclusion, Ferroptosis plays a nonnegligible role in LUAD. Exploration of the ferroptosis pattern will enhance the prognostic stratification of individual patients and move towards the purpose of personalized treatment.